Perceraian Bagi Masyarakat Hindu di Bali yang Tidak Mempunyai Akta Perkawinan - I Made Dwi Mahardika; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
There are many cases of divorce for Hindus in Bali, especially for marriages that do not have a marriage certificate. This study aims to determine the arrangements for divorce for those who are not married and the legal consequences for society, especially in Bali, for divorce, especially for those who are not married. The study method is a normative type of study, with a statutory and conceptual approach. Legal materials consist of primary, secondary and tertiary. Data were collected through literature study and analyzed descriptively based on deductive-inductive legal logic. The results of the study indicate that marriage arrangements for those who do not have marriages are not regulated in the Law or PP regarding marriage and how the legal consequences for the community, especially in Bali, for divorce, especially for those who do not have marriages are basically not recognized because they are not registered under administrative law because Marriage or divorce is legal according to Hinduism only, but in the District Court the divorce must be proven by a marriage certificate from the village head then the divorce process can occur. The author suggests that marriages should be carried out so that they are religiously legal or recorded in the state so that they are also legal under state or national law